Limiting the collegiality of adjudication - in civil cases - as a violation of democracy. - Adamiec-Witek, Mariola (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
The author discusses the regulations limiting collegiality in adjudication in civil cases - including in the second instance - introduced successively since 1965, with particular emphasis on the changes introduced in 2021 and then in 2023, indicates the effects of these regulations on adjudication and the reaction of the legal community to the introduction of this regulation - emphasizing the violation of democracy as a result of these changes. The author also indicates how the issue of collegiality in adjudication has been regulated in legislation - since Poland regained independence.